A Pattern and Polarization Reconfigurable Liquid Metal Helical Antenna - Amit Mehta (2018 IEEE International Symposium on Antennas and Propagation & USNC/URSI National Radio Science Meeting, 2018)
A pattern and polarization reconfigurable helix antenna with mechanically actuated liquid metal in a helical channel is presented for L1 frequency band (1.575 GHz). The antenna is composed of a flexible polymer tube shaped into a helix which is filled in and out with a peristaltic micropump. The micropump is controlled using a Raspberry Pi computer via an H-bridge DC circuit which can continuously adjust direction and speed of the pump. The Antenna generates four types of beams i.e., linearly polarized semi-doughnut and axial beams; elliptically and circularly polarized axial beams. The corresponding maximum gains are 1.1 dBi, 5.9 dBi, 7.6 dBi and 8.5 dBi for the four beams.